88.7k views
0 votes
3(7x-1)=4x+6 please answer me at least two or three people ​

User Dhahn
by
4.8k points

2 Answers

3 votes

3 ( 7x - 1 ) = 4x + 6

  • solve the bracket first
  • multiply 3 and 7x to get 21x
  • multiply 3 and negative 1 to get negative 3

21x - 3 = 4x + 6

  • combine the terms that are alike

21x - 4x = 6 + 3

  • add / subtract the terms

17x = 9

  • divide 9 by 17

x = 9 / 17

  • the answer is

x = 0.5294117647

hope that helps :))

User Drizzd
by
4.5k points
5 votes

Answer:

x = 9/17

Explanation:

3(7x-1)=4x+6 distribute

21x - 3 = 4x + 6 combine similar terms

21x - 4x = 6 + 3 simplify

17x = 9

x = 9/17

User Gregory Bell
by
4.8k points